Correction to: Non-communicable disease prevention policy process in five African countries - Pamela A. Juma; Shukri F. Mohamed; Beatrice L. Matanje Mwagomba; Catherine Ndinda; Clarisse Mapa-tassou; Mojisola Oluwasanu; Oladimeji Oladepo; Opeyemi Abiona; Misheck J. Nkhata; Jennifer P. Wisdom; Jean-Claude Mbanya (BMC, 2018)
After publication of the article [1], it was noticed that the title has erroneously included 'authors' in the end.